Efficiency and Interference Verification of a HONO Collection System Using an Ultrasonic Nozzle Coupled with a Recirculating Spray Chamber for Ambient Air Monitoring - Sea-Ho Oh; James J. Schauer; Hajeong Jeon; Dong-Hoon Ko; Seoyeong Choe; Min-Suk Bae (Applied Sciences, 2024)
This study explores the efficiency and applicability of a HONO collection system that incorporates an ultrasonic nozzle and spray chamber for the measurement of ambient air. The system demonstrates (1) a remarkable efficiency of 97.7% across two serial stages, (2) lower detection limits of 0.15 ppbv for HONO, and (3) an absence of interference from NO2 or OH radicals. Practical ambient monitoring with the HONO collection system revealed typical diurnal variations in HONO, O3, and HNO3 concentrations, aligning with photolysis dynamics. Notably, HONO concentrations peaked at 0.37 ppb during nighttime and decreased to 0.27 ppb by midday. O3 demonstrated an inverse relationship with HONO, especially during ozone depletion phases, with r2 values of 0.94, 0.81, and 0.52 across various intervals. The HONO/NOx ratio during periods of enhanced HONO suggested the presence of additional formation mechanisms beyond heterogeneous NOx reactions. Moreover, ozone levels often fell below 20 ppb, indicating a consistent inverse correlation with HONO, thereby reaffirming further mechanisms of HONO formation beyond heterogeneous NOx reactions. The real-time atmospheric chemical reactions involving HONO, monitored concurrently with O3 and NOx, were effectively validated by the HONO collection system employed in this investigation.